Attributes Influencing Retail Store Choice Decision of Shoppers: A Case of Pune City. (December 2017) - Desai, Devang; Phadtare, Milind
The consumer markets in India are expected to reach about US$1.5 trillion from the existing US$750 billion by 2021. Emergence of new retail formats and entry of new players in every format is also likely to increase competition in Indian retail sector. It has, thus, become important for the retailers to know how shoppers choose a store from various options available to them. The article aims to achieve data reduction while identifying various store attributes that influence the choice of stores by shoppers while purchasing grocery items from supermarkets. We collected primary data from 300 shoppers using personally administered questionnaire in select supermarkets in Pune. We used exploratory factor analysis to identify the attributes and the factor structure. We then used confirmatory factor analysis to validate the same. Thus, we developed a scale consisting of nine store attributes converging under two factors to understand shoppers' decision to choose a particular supermarket for their grocery purchases.